Pengaruh Penambahan Zat Aditif Pada Pengecoran Beton Joint Pit SKTT 150 kV Sario – Teling - Fitrianto, Andrian Juli; Hakam, Dzikri Firmansyah; Prahastono, Iswan; Nainggolan, Akiman (ROTASI, 2021)
The construction of a 150 kV Sario - Teling High Voltage Cable Line (SKTT), which located in the city of Manado - North Sulawesi Province, is an important electricity project that has been planned to operate in 2020 according to the 2019-2028 Rencana Umum Penyediaan Tenaga Listrik (RUPTL). This transmission line construction is expected to increase electrical energy services in North Sulawesi region. This SKTT project applied the Boring Horizontal Directional Drilling (HDD) method to install the 150 kV SKTT cable. On the other hand, the Joint Pit installation uses a Box Culvert precast construction consisting of reinforced concrete.From the test results of the samples, we can conclude that there were an increases in the compressive strength of concrete from 1,04% to 1,27% above the compressive strength of normal concrete. There was a decrease in the compressive strength of the concrete at several points. However, this anomaly is still above the minimum limit of concrete compressive strength determined by PLN, which is 400 kg / cm2.This study involved laboratory testing to determine the effect of additives added during Box Culvert casting in order to obtain an efficient hardening time. It is hoped that this study will have an impact on the completion of the SKTT 150 kV Sario - Teling project on time, so that it can provide economic benefits for PLN and the consumer.